On the agenda: The challenges for the preservation of school heritage - Leon , Adriana Duarte; Roschild, Adriana Barboza; Rodrigues , Tobias de Medeiros; Garcia, Márcio Pereira; Machado, Carolina Ceno; Villar, Waleska Ribeiro; Porto , Júlia Petiz (Seven Editora, 2024)
The objective of this reflection is to present the research called "The digitization of the Institutional Collection as a possibility of Preserving the Memory of Professional and Technological Education" and to announce some of the possibilities identified in the use of technology for the preservation of institutional memory. Understanding that the conscious appropriation of the history of an institution makes it possible to signify and resignify its identity and social function, we seek to stimulate other actions in the context of preserving the history and memory of school institutions. DOI:https://doi.org/10.56238/sevened2024.026-001